Poland in the British Parliament 1939-1945 : Volume 1 : British guarantees to Poland to the Atlantic Charter (march 1939 - august 1941) - Jedrzejewicz, Waclaw (New York : Josef Pilsudski Institute of America for Research in the modern history of Poland, 1946)
Bibliotheek Camille Huysmans
Engels
Meerdelige publicatie
Keywords: Wereldoorlog 2; Brits-Poolse relaties; Polen